Locoregional cancer therapy using polymer-based drug depots. Issue 4 (April 2016) - Ramazani, Farshad; van Nostrum, Cornelis F.; Storm, Gert; Kiessling, Fabian; Lammers, Twan; Hennink, Wim E.; Kok, Robbert J.
Graphical abstract: Highlights: Polymer-based drug depots improved the median survival of patients with malignant gliomas. Porous microparticles hold promise for treatment of lung cancer by inhalation. Trans-arterially injected drug-eluting microparticles block tumor perfusion and release drug locally. Intraperitoneally injected microparticles allow local treatment of abdominal cancer. Abstract : Locoregional delivery of anticancer drugs is an attractive approach to minimize adverse effects associated with intravenous chemotherapy. Polymer-based drug depots injected or implanted intratumorally or adjacent to the tumor can provide long-term local drug exposure. This review highlights studies in which drug-eluting depots have been applied locally in the treatment of cancer. In many cases such drug depots are used for prevention of tumor recurrence after surgery to eradicate remaining tumor cells. Clinical success has been reported for the treatment of brain cancer and liver cancer, and preclinical studies showed proof-of-concept for inhaled drug depots in lung cancer and intraperitoneally injected depots for the treatment of abdominal cancer.